1999
DOI: 10.1093/genetics/153.4.1535
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae G1 Cyclins Are Differentially Involved in Invasive and Pseudohyphal Growth Independent of the Filamentation Mitogen-Activated Protein Kinase Pathway

Abstract: Several lines of evidence suggest that the morphogenetic transition from the yeast form to pseudohyphae in Saccharomyces cerevisiae may be regulated by the cyclin-dependent kinase (Cdk). To examine this hypothesis, we mutated all of the G1 cyclin genes in strains competent to form pseudohyphae. Interestingly, mutation of each G1 cyclin results in a different filamentation phenotype, varying from a significant defect in cln1/cln1 strains to enhancement of filament production in cln3/cln3 strains. cln1 cln2 doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(11 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Therefore, cell-cycle regulation of the fMAPK pathway occurs before Ste11p and at the level of Msb2p and Sho1p. Consistent with the role of the fMAPK pathway in delaying cellcycle progression in G1 (Loeb et al, 1999;Madhani et al, 1999) and G2/M (Ahn et al, 1999;Rua et al, 2001;Vandermeulen and Cullen, 2020), Ste11p-4 showed a delay in Clb2p-HA accumulation (Fig. 2A, compare wild type at 60 min with STE11-4 at 60 min).…”
Section: Expression Of the Gene Encoding The Mucin Sensor Msb2p Is Cell-cycle Regulatedsupporting
confidence: 76%
See 1 more Smart Citation
“…Therefore, cell-cycle regulation of the fMAPK pathway occurs before Ste11p and at the level of Msb2p and Sho1p. Consistent with the role of the fMAPK pathway in delaying cellcycle progression in G1 (Loeb et al, 1999;Madhani et al, 1999) and G2/M (Ahn et al, 1999;Rua et al, 2001;Vandermeulen and Cullen, 2020), Ste11p-4 showed a delay in Clb2p-HA accumulation (Fig. 2A, compare wild type at 60 min with STE11-4 at 60 min).…”
Section: Expression Of the Gene Encoding The Mucin Sensor Msb2p Is Cell-cycle Regulatedsupporting
confidence: 76%
“…Another target of the fMAPK pathway, BUD8 (Adhikari and Cullen, 2014), which marks the distal pole and is required for distal budding during filamentous growth (Taheri et al, 2000;Harkins et al, 2001;Cullen and Sprague, 2002), is tightly regulated throughout the cell cycle to ensure proper cell polarity (Schenkman et al, 2002). During filamentous growth, the fMAPK pathway induces a delay in the cell cycle by stimulating expression of the gene encoding the G1 cyclin Cln1p (Loeb et al, 1999;Madhani et al, 1999). Therefore, the cell-cycle regulation of a MAPK pathway may impart cell-cycle regulation to target genes to ensure that aspects of the morphogenetic response are tightly coordinated.…”
Section: Cell-cycle Regulation Of Mapk Pathway Activitymentioning
confidence: 99%
“…Like for adhesion, the roles pathways play in regulating cell elongation and distal budding may also differ between pathways. The MAPK pathway is known to regulate cell elongation by extending the G1 phase of the cell cycle [174] by regulating expression of CLN1 [160,175], which results in prolonged growth at the tip of the cell. The role of the other pathways in regulating cell elongation have not been fully explored.…”
Section: The Mapk Pathway Is the Main Regulator Of Cell Elongation And Distal Budding During Invasive Growthmentioning
confidence: 99%
“…First, deletion of genes, involved in the cell cycle and regulated by MBF, cause abnormal budding ( 33 ). Second, MAPK induces cell elongation by regulating CLN1 ( 34 ), a gene essential for pseudohyphal growth ( 35 , 36 ). In addition, there is some interaction between MBP1 and CLN1 ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, since Mbp1p/MBF regulates many genes involved in the cell cycle ( 24 , 28 , 30 , 32 , 33 , 38 40 ), MBP1 may associate with another gene linked to the filamentous phase, for example, CLN3 . CLN3 has an antagonistic effect on pseudohyphal growth ( 35 ), and the inhibitory effect might be mediated through MBP1 . Support for this hypothesis includes the interaction between them; CLN3 is an activator of MBF ( 39 ), and the role of CLN3 in the regulation of cell size and budding is partly dependent on MBF ( 39 ).…”
Section: Discussionmentioning
confidence: 99%